Tecendo os fios das identidades: implicações da performatividade na construção da identidade profissional dos professores da Universidade Federal do ABC (UFABC) - Santos, Sandra Rosa Gomes dos (2020)
The present research work focuses on the professional identity of higher education professors, having the federal university of ABC as a research universe, researching the construction of their professor's' professional identity and its relationship with performativity and continuing education. The research problem results from the fact that the Federal University of ABC (UFABC) is a new model of higher education, with innovative principles (social inclusion, interdisciplinarity, new pedagogical model, excellence) that may influence the construction or reconstruction of the professional identity of they professors. The institution is subject to the same national and international requirements that regulate other universities and is subject to external evaluations, with its professors having productivity goals, working for objectives, and being evaluated for their performance and effectiveness. The research question resulting from the stated problem, and which guided us, was the following: what are the principles and processes that regulate the construction of the professional identity of UFABC professors and their relationship with performativity and continuing education? We believe that the construction, crisis and reconstruction of identities is a topic of enormous academic interest, taking into account the implications of neoliberal policies and the requirements of multilateral regulatory agencies in defining, monitoring and evaluating the results and impacts of policies. A new world educational order is being built, transforming education into a market product. From an epistemological point of view, we adopted post-critical and post-colonial theories as a theoretical foundation, insofar as they allowed the approach of the research object in a critical and counter-hegemonic perspective. Methodologically, we adopted a qualitative approach with the use of interviews as a data collection instrument and discourse analysis, as a data analysis technique. The fundamental categories were identity, professional identity, identity and performativity and identity and training. The documentary analysis carried out allows us to affirm that the professional identity of professors is configured according to the international requirements for higher education. The empirical work carried out allowed us to conclude that the thesis from which we start is confirmed, that is, that there is a relationship between the construction of professional identities, performativity and continuing education, which is understood by the subjects, above all, as research.